A Comparative Study: First Canadian Tamil Scholar Rv. G.U. Pope’s Best Thirukkural Reinvention - Thurairajah , Uthayan (Research Highlights in Language, Literature and Education Vol. 9, 2023)
The study aims to compare the English translation of Thirukkural by G. U. Pope with other translations and identify his ontological and epistemological contribution to the Tamil language and literature. Though Language provides the ability to imagine and interpret the text, linguistic untranslatability often arises due to the problem of symbolic meaning. A word could have different kinds of meaning through its etymology and association. While all translators are not creative writers, their suggestions of words could always be diverse. But a translator's job is to reactivate the text from the active one. Many problems and deficiencies in translation need more attention. Language has its history, culture, heritage, and tradition and is a communication tool and a living guide for human beings. A poor translation can lead to confusion when most native ideas are unfamiliar to foreign translators. Therefore, it perishes the text's originality when translated into a foreign language. This research paper is a deep comparative and comprehensive analysis of the reinvention of Thirukkural by G. U. Pope with three other translators at different times. The translation may have many shortcomings based on the translator's knowledge of the source and target languages and ontological and epistemological approaches to handling the translation without compromising the original meaning of the source text. It is complex and difficult to assess or reach a consensus since each translator's knowledge level and understanding of the subject matter differ. The comparative assessment uses various tools to evaluate the quality of the translation. This paper makes a comprehensive study to find the best Thirukkural translation using the CUTER assessments, BATMAN assessments of the source language, and SAFEMAN assessments of the target language and bring light to translation challenges. The source and target language assessments bring significant findings that benefit society and future translators. This is the first research paper to address all these parameters comprehensively. Therefore, this research finding is historical and ground-breaking in translation, culture, and linguistics education. This paper will help researchers, translators, linguistics, educators, students, educational institutions, and society.